Is Zuspan Regimen Adequate for Preventing Eclampsia?: A Case Report - Raymond Surya; Budi Iman Santoso; Surahman Hakim (Faculty of Medicine Universitas Padjadjaran, 2018)
Magnesium sulphate (MgSO4) is believed to treat preeclampsia and eclampsia for more than a century with a total dose of MgSO4 varying from 2 to 5g per 24 hours. Zuspan and Pritchard are two internationally recommended regimens that are accepted as the standard regimen. In this case report, we presented a 41 year old woman with puerperal preeclampsia prescribed with a complete Zuspan regimen. She had eclamptic seizure after completing Zuspan regimen with Mg SO4 level of 4.3 mg/dL. In this case, the possibility of eclamptic seizures might be due to a lack of MgSO4 dose. The administration of MgSO4 for preeclampsia with severe features and prophylactic of eclampsia should be adjusted.